Pembelajaran Berbasis Etnosains dalam Konteks Pendidikan Kimia: Kajian Sistematik Terhadap Tren Pendekatan dan Aplikasinya - Munawwarah, Munawwarah; Alqadri, Zulqifli (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This study aims to identify the trends in approaches and applications of ethnoscience-based learning media in chemistry education through a Systematic Literature Review. The urgency of this research lies in the need for contextual learning approaches that are relevant to local culture. A total of 19 relevant articles from national and international journals were selected from an initial pool of 30 articles. The selection procedure included identification, reduction, and content analysis based on inclusion criteria. The analysis revealed the dominance of ethnoscience modules (31.58%), followed by miscellaneous media and textbooks (each 15.79%). These media contribute to improving students' chemistry literacy, science process skills, and culturally based character development. This study recommends developing more diverse and integrative ethnoscience-based learning media.